The effect of pentoxifylline on intestinal ischemia/reperfusion injury - ŞENER, GÖKSEL (My University, 2001)
The small intestine is highly sensitive to oxygen free radical-induced injury. Post-ischemic intestinal tissue damage appears to be due to the formation of oxygen radicals. Free radical initiated lipid peroxidation (LP) following intestinal ischemia/reperfusion (I/R) may disrupt mucosal integrity. Indirectly, the radicals trigger the accumulation of neutrophils within the affected tissue, initiating inflammatory processes that lead to severe mucosal lesions. In the present study we investigated the effect of pentoxifylline (PTX), a potent inhibitor of tumour necrosis factor production, on I/R induced intestinal injury. Wistar albino rats were divided into four groups: (1) Sham operation (S); (2) Sham operation + PTX (50 mg/kg i.v.) (S + PTX); (3) 1 h ischemia + 2 h reperfusion (I/R); and (4) I/R + PTX. Animals were sacrificed at the end of the reperfusion period and ileum samples were obtained. Malondialdehyde (MDA) levels, an end product of LP, glutathione (GSH) levels, a key antioxidant, and myeloperoxidase (MPO) activity (an index of polymorphonuclear neutrophils) stimulation, were determined in ileum homogenates. The results of the present study indicate that ischemia/reperfusion results in a significant increase in MDA content and MPO activity with a significant decrease in GSH content. Treatment with PTX returns these biomarkers to control values. A mechanism of this protective effect may involve inhibition of neutrophil oxidative burst.
Keywords: Glutathione; Intestinal ischemia; Lipid peroxidation; Myeloperoxidase; Pentoxifylline; Reperfusion